Peningkatan Keterampilan Guru Dalam Mengajar Dengan Teknik Pembelajaran Berbasis Powerpoint Melalui Pola Bimbingan Individu Di SMAN 2 Tarutung Semester 2 Tahun Pelajaran 2018/2019 - Belman Panjaitan (Intersections, 2022)
This research is school action research. The research subjects were 8 teachers. Data collection methods in this study are observation, and documentation. Data validation was done by triangulation technique. Data analysis was done by descriptive technique. The results of the study showed that the skills of teachers in teaching with powerpoint-based learning techniques increased. The increase in the average value of the observations from 47.29 with LESS criteria, in the initial conditions, to 65.63 with ENOUGH criteria in the first cycle and in the last cycle to 83.54 with VERY GOOD criteria. Individual skill improvement improved in each cycle, namely 0% in the initial conditions, increased to 25% or 2 teachers in the first cycle and increased to 8 teachers or 100% in the last cycle with an explanation of 5 teachers or 62.50% in the criteria VERY GOOD and 3 teachers or 37.50% in GOOD criteria